Reviewing the implementation of the Smart Schools and the training of Bestari Teachers in Malaysia - Shaharudin, Balkisnah; Zainal Abiddin, Norhasni (Journal of International Social Research, 2009)
Smart Schools (Sekolah Bestari) and In cultured schools with Smart Technology (Pembestarian Sekolah) into institutions of excellence are two statements which discuss the direction of national education. This paper seeks to clarify the concept of Smart Schools and the in cultured schools with smart technology into institutions of excellence as a national agenda of utmost importance for the realization of Malaysia as a developed nation. This paper will outline the chronology of Bestari (Excellence) training which had been carried out in the period from 1998 to 2008. This article will also examine the concept of transfer of training specifically for the rationale and importance of Bestari training. Subsequent to that it will touch on some study papers on the training of Bestari teachers with the aim of assessing the extent of training transfer that had taken place amongst teachers who have attended the courses and related training – this is to highlight what have been done in Bestari training. It is hoped that, with this essay, the essentials of Bestari training from the aspects of support and hindrances can be identified and efforts for the improvements of training can be made from time to time.